Ambient Air Pollution Associated with Suppressed Serologic Responses to Pneumocystis jirovecii in a Prospective Cohort of HIV-Infected Patients with Pneumocystis Pneumonia - Blount, Robert J.; Djawe, Kpandja; Daly, Kieran R.; Jarlsberg, Leah G.; Fong, Serena; Balmes, John; Miller, Robert F.; Walzer, Peter D.; Huang, Laurence (PloS one, 2013)
Ambient air pollution (AAP) may be associated with increased risk for Pneumocystis pneumonia (PCP). The mechanisms underlying this association remain uncertain. To determine if real-life exposures to AAP are associated with suppressed IgM antibody responses to P. jirovecii in HIV-infected (HIV+) patients with active PCP, and to determine if AAP, mediated by suppressed serologic responses to Pneumocystis, is associated with adverse clinical outcomes. We conducted a prospective cohort study in HIV+ patients residing in San Francisco and admitted to San Francisco General Hospital with microscopically confirmed PCP. Our AAP predictors were ambient air concentrations of particulate matter of < 10 µm in diameter (PM10) and < 2.5 µm in diameter (PM2.5), nitrogen dioxide (NO2), ozone (O3), and sulfur dioxide (SO2) measured immediately prior to hospital admission and 2 weeks prior to admission. Our primary outcomes were the IgM serologic responses to four recombinant P. jirovecii major surface glycoprotein (Msg) constructs: MsgC1, MsgC3, MsgC8, and MsgC9. Elevated PM10 and NO2 exposures immediately prior to and two weeks prior to hospital admission were associated with decreased IgM antibody responses to P. jirovecii Msg. For exposures immediately prior to admission, every 10 µg/m(3) increase in PM10 was associated with a 25 to 35% decrease in IgM responses to Msg (statistically significant for all the Msg constructs), and every 10 ppb increase in NO2 was associated with a 19-45% decrease in IgM responses to Msg (statistically significant for MsgC8 and MsgC9). Similar findings were seen with exposures two weeks prior to admission, but for fewer of the Msg constructs. Real life exposures to PM10 and NO2 were associated with suppressed IgM responses to P. jirovecii Msg in HIV+ patients admitted with PCP, suggesting a mechanism of immunotoxicity by which AAP increases host susceptibility to pulmonary infection.